Crystallization of N-terminal Strep-tagged Fusion Lipase from Thermostable Bacillus sp. Strain 42. - Basri, Mahiran; Raja Abd Rahman, Raja Noor Zaliha; Tengku Abdul Hamid, Tengku Haziyamin; Salleh, Abu Bakar (IUCr, 2009)
Lipases have great potential to be used in industries due to their favourable properties such as substrate specific, enantiomerically selective, regioselective and mild reactions conditions. Lipases of microbial origin are generally more stable than lipases from animal or plant and as such they are useful source for industrial enzymes. A 1.2 kb lipase gene (AY 78735) [1], isolated from solvent stable and thermostable Bacillus sp. strain 42 was overexpressed using pET51b vector with E. coli host strain BL21(DE3) pLysS, in which the fusion lipase contains N-terminal Strep-tag II affinity tag [2]. The purified fusion lipase, at protein concentration of about 4.0 mg/mL, was induced to crystallize in 0.1 M MES buffer at pH 6.5 without the presence of salt, but in the presence of only 12% w/v PEG 20 000 as precipitant. Crystallization reactions were carried out using vapour diffusion methods at 16˚C. Crystals were formed after 12 hours incubation. The crystals with size measuring around 0.04 X 0.12 mm were shown to be heavily stained with protein dyes. Lip 42 lipase is highly homologous to three crystallized lipases from thermophilic Bacillus sp., namely T1 lipase [3], P1 lipase [4] and L1 lipase [5]. Lip 42 protein crystals, despite having almost 97% similar homology in amino acid sequence, showed a different shape and crystallization condition. The shape of Lip 42 crystal appeared to be partly attributed to the presence of N-terminal tag.